High-resolution fully-polarimetric synthetic aperture radar dataset - R. Derek West; Amelia Henriksen; Eric Steinbach; Mohamed S. Ebeida (Discover Geoscience)
Abstract Objectives Fully-polarimetric synthetic aperture radar (PolSAR) data contain a rich body of elementary scattering physics information that is critically valuable for a broad range of applications and scientific purposes. However, there is a lack of available high-resolution (< 0.3048-m) data available for PolSAR phenomenology research. This article introduces a high-resolution PolSAR data set collected and provided by Sandia National Laboratories (SNL). The data sets were collected to support studying high-resolution scattering physics from different types of clutter and applications such as polarimetric-based terrain classification. Data description The data set presented consists of 39 200 m × 200 m complex-valued PolSAR image sets with 0.12-m (~ 4.7-inch) resolution and is the result of two different collection campaigns, one campaign in 2013 and the other in 2015. The data sets were collected with SNL’s airborne fully-polarimetric X-band (9.6 GHz center frequency) radar system and contains a variety of natural and cultural clutter environments with scene content ranging from agricultural fields to urbanized areas collected throughout the greater Albuquerque, New Mexico, U.S.A. region.